2015
DOI: 10.1093/femspd/ftv044
|View full text |Cite
|
Sign up to set email alerts
|

HIV-associated lymphoma in the era of combination antiretroviral therapy: shifting the immunological landscape

Abstract: HIV infection increases the risk of many types of cancer, including lymphoma. Combination antiretroviral therapy (cART) has reduced, but not eliminated, the risk of HIV-associated lymphoma. There has been a substantial shift in the subtypes of lymphoma observed in HIV-infected patients treated with cART. In this review, we will first outline these changes based on epidemiological studies and describe the impact of cART on lymphoma risk and mortality. Then, we will discuss some immunological factors that may co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1
4

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 74 publications
0
16
1
4
Order By: Relevance
“…Effective NK cell cytolytic function requires delicate balance between the activating and inhibitory receptors [ 8 ]. Downregulation of the receptors during chronic HIV infection has been associated with risk of development non-AIDS-defining cancers [ 28 , 29 ]. Low NKp46 receptor expression was previously reported after three years of HIV treatment in a European cohort, where it improved with increasing duration of ART [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Effective NK cell cytolytic function requires delicate balance between the activating and inhibitory receptors [ 8 ]. Downregulation of the receptors during chronic HIV infection has been associated with risk of development non-AIDS-defining cancers [ 28 , 29 ]. Low NKp46 receptor expression was previously reported after three years of HIV treatment in a European cohort, where it improved with increasing duration of ART [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even though HL is not an AIDS-defining illness, the incidence of cHL is 10-fold higher than in the general population, and essentially all of that increase involves EBV-positive tumours of mixed cellularity or lymphocyte-depleted subtypes [ 60 ]. Just as with BL, the development of HIV-related HL is not dependent on profound T cell impairment; indeed cHL incidence among HIV carriers has slightly increased after the introduction of HAART [ 16 ]. Interestingly these tumours tend to arise somewhat later than HIV-related BL, in patients with relatively modest reductions in CD4 + T cell counts.…”
Section: Hodgkin Lymphomamentioning
confidence: 99%
“…Previous studies have shown that the combination of cART with chemotherapy increased overall survival of these patients [ 3 5 ]. However, even in well-treated HIV-positive patients, the results of lymphoma treatment are, although improving, still not as good as in HIV-negative patients [ 6 8 ]. Apart from the HIV infection itself, drug–drug interactions between cART and cytostatics may play an important role in the treatment outcome of patients.…”
Section: Introductionmentioning
confidence: 99%